The Impact of Rainfall and Rainy Days on Tobacco Crop (Nicotiana tabacum L.) in PTPN II Division of Klumpang - Aprianto Aprianto; Ratna Rosanty Lahay; Irsal Irsal (Universitas Sumatera Utara, 2017)
This study aims to determine the effect of rainfall and rainy days as well as the correlation of both on Tobacco Crop production in 2012 - 2014 in PTPN II Divisi of Klumpang Hamparan Perak District of Deli Serdang. The analytical method used is multiple linear regression analysis and correlation analysis. The model was tested for feasibility with classic assumption test including normality test, heteroscedasticity test, multicolinearity test, and autocorrelation test by using statistical tools SPSS.v.18 for windows.The results showed that variable rainfall and rainy day have a real effect on alpha 5% (Sig> α 0.05) to increased production of Leaf Tobacco In 2012 - 2014. Correlation results in crop years 2012 - 2014 with two-way analysis at the level of 1% and 5% test showed variable rainfall and rainy days have a strong relationship, real and (positive) direction. Correlation value of rainfall and rainy days in a row is 0.943 (0,005)with a significance value <α 0:01. Variable tobacco production with rainfall and rainy days have a strong relationship but (negative)direction with value correlation -0,926 (0,008) with significance < α 0.01 and -0,811 (0,050) with significance < α 0.05.